Erratum: Lagunday, N.E. & Amoroso, V.B. (2025) Nepenthes maagnawense (Nepenthaceae), a new species of pitcher plant from Mt. Maagnaw, Kitanglad Range, Bukidnon, Central Mindanao, Philippines. Phytotaxa 693 (1): 87‒94. - Lagunday, Noel E.; Amoroso, Victor B. (Phytotaxa, 2025)
N/A